Approximating the moments of a spatial point process - Baddeley, Adrian; Nair, G. (2012)
© 2012 John Wiley & Sons, Ltd. We propose a "Poisson-saddlepoint" approximation to the first and second moments of a spatial point process of Gibbs type. In the examples studied, the approximation is accurate, and fast to compute. We demonstrate applications to data analysis and simulation.